Early and late stage gene therapy interventions for inherited retinal degenerations. (January 2022) - Botto, Catherine; Rucli, Marco; Tekinsoy, Müge Defne; Pulman, Juliette; Sahel, José-Alain; Dalkara, Deniz
Abstract: Inherited and age-related retinal degeneration is the hallmark of a large group of heterogeneous diseases and is the main cause of untreatable blindness today. Genetic factors play a major pathogenic role in retinal degenerations for both monogenic diseases (such as retinitis pigmentosa) and complex diseases with established genetic risk factors (such as age-related macular degeneration). Progress in genotyping techniques and back of the eye imaging are completing our understanding of these diseases and their manifestations in patient populations suffering from retinal degenerations. It is clear that whatever the genetic cause, the majority of vision loss in retinal diseases results from the loss of photoreceptor function. The timing and circumstances surrounding the loss of photoreceptor function determine the adequate therapeutic approach to use for each patient. Among such approaches, gene therapy is rapidly becoming a therapeutic reality applicable in the clinic. This massive move from laboratory work towards clinical application has been propelled by the advances in our understanding of disease genetics and mechanisms, gene delivery vectors, gene editing systems, and compensatory strategies for loss of photoreceptor function. Here, we provide an overview of existing modalities of retinal gene therapy and their relevance based on the needs of patient populations suffering from inherited retinal degenerations. Graphical abstract: Image 1